You are on page 1of 4

# Homogeneous linear ODEs with

constant coefficients
• We shall
h ll now consider
d second d order
d homogeneous
h l
linear ODEs whose
h
coefficients a and b are constant.
y + ay + byy = 0

## Mathematical background • The solution of a first order linear ODE:

y + ky = 0
• By separating variables and integrating, we obtain:
dy
= −kdx ln y = − kdx + c *
Homogeneous linear ODEs with
•Homogeneous y
• Taking exponents on both sides:
constant coefficients y ( x) = ce
− kdx
= ce − kx
• Let’s tryy the above solution in the first equation.
q Usingg a constant
N h
•Nonhomogeneous ODE
ODEs coefficient k: x
y=e
x
Substituti ngg its derivatives : y = e x
and y = 2
e
( 2
+ a + b )e x = 0

## Homogeneous linear ODEs with

Introduction
constant coefficients
• Th
The dynamic
d i behaviour
b h i off mechanical
h i l systems
t i described
is d ib d by
b what
h t • Hence iff λ is a solution
l off the
h important characteristic
h equation (or
(
we call second order Ordinary Differential Equations. auxiliary equation)
2
+a +b = 0
• The input to the mechanical structure appears on the right hand • Then the exponential solution y = e x is a solution of the
side of the equation and is the Force and the solution of the
equation gives the output which is usually the displacement. y + ay + byy = 0

• In order to be able solve these equations, it is imperative to have a • Now from elementary algebra we recall that the roots of this quadratic
solid background
g on the solution of homogeneous
g and equation are: 1
= ( −a + a 2 − 4b)
nonhomogeneous Ordinary Differential Equations. 1
2
1
2 = ( −a − a 2 − 4b)
2
• Homogeneous Ordinary Differential Equations represent the ‘Free
Free
Vibrations’ and the non homogeneous Ordinary Differential • The functions below are solutions to y + ay + by = 0
Equations represent ‘Forced Vibrations’. y1 = e 1x
and y2 = e 2x
Homogeneous linear ODEs with Homogeneous linear ODEs with
constant coefficients constant coefficients
• From algebra
l b we know
k that
h the
h quadratic
d equation below
b l may have
h three
h CASE II: Reall double
d bl root = a/2 /
kinds of roots: • We have : (u y1 + 2u y1 + uy1 ) + a(u y1 + uy1 ) + buy1 = 0
2
+a +b = 0
• Collecting terms u y + u (2 y + ay ) + u ( y + ay + by ) = 0
1 1 1 1 1 1

## • Case I: Two real roots if a − 4b > 0 2

• This expression in the last paranthesis is zero, since y1 is a solution of
• Case II: A real double root if a 2 − 4b = 0 y + ay + by = 0
• Case III: Complex conjugate roots if a 2 − 4b < 0 • The expression in the second paranthesis is zero too since
2y 1 = − ae − ax / 2 = −ay1

## • We are thus left with

case a basis of solutions of y + ay + by = 0
• CASE I: In this case, u y1 = 0
x
in any interval is: y1 = e and y2 = e
x 1 2 Hence
u =0
because y1 and y2 are defined and real for all x and their q
quotient is not
By two integrations
constant. The corresponding general solution is:
1x 2x
u = c1 x + c2
y = c1e + c2 e

## Homogeneous linear ODEs with Homogeneous linear ODEs with

constant coefficients constant coefficients
CASE II: Reall double
d bl root = a/2 / CASE II: Reall double
d bl root = a/2 /
• If the discriminant a 2 − 4b is zero, we see from To get a second independent solution y2=uy1, we can simply choose c1=1
1 and c2=0 and take u=x. Then y2=xyy1. Since these solutions are not
= ( −a + a 2 − 4b)
1
2 proportional, they form a basis. Hence in the case of a double root of
1
2 = ( −a − a 2 − 4b)
2
+a +b = 0
2
a basis
b i off solutions
l i off y + ay + by
b =0
that we get only one root: = 1 = 2 = − a / 2,
hence only one solution : on any interval is: e − ax / 2 , xe − ax / 2
y1 = e − ( a / 2 ) x

TTo obtain
b i a secondd independent
i d d solution
l i y2 needed
d d for
f a basis,
b i we use the
h
method of order of reduction. Setting • The corresponding general solution is: y = (c1 + c2 x )e − ax / 2
y2 = uy1 , Substituti ng this and its derivatives y 2 ' = u ' y1 + uy1 ' and y2 ' ' into

y + ay + by = 0
Homogeneous linear ODEs with Homogeneous linear ODEs with constant coefficients:
P f
Proof
constant coefficients Complex number representation of harmonic motion

## CASE III: Complex roots –a/2+i

a/2+i and –a/2
a/2 i
• This case occurs if the discriminant of the characteristic equation
2
+a +b = 0
X = OP
is negative. In this case, the roots of the above equation and thus the solutions of the ODE
come at first out complex. However, we show that from them we can obtain a basis of real solutions:
y + ay + by = 0 X = a + ib
X
where y 1 = e − ax / 2 cos x, y 2 = e − ax / 2 sin
i x
1
2
= b − a2
4
• This is proved in the next slides. It can be verified by substitution that these are solutions in the present
case. They form a basis on any interval since their quotient cotωx is not constant. Hence, a real general
solution
l ti ini Case
C III is:
i
y = e − ax / 2 ( A cos x + B sin x) ( A , B arbitrary )

## Homogeneous linear ODEs with Homogeneous linear ODEs with

constant coefficients: Proof constant coefficients: Proof
• Complex
l number
b representation off harmonic
h motion: Since • As
A apparentt we have
h t complex
two l roots.
t These
Th are:
X = OP 1 =
1
2
a +i and 1 =
1
2
a −i
this vector can be represented as a complex number:
• We know from basic mathematics that a complex exponential function can
X = a + ib be expressed as: r + it r it r
where i = − 1 and a and b denote x and y components of X . Components e = e e = e (cos t + i sin t )
a and b are also called the real and the imaginary parts of the vector X. If A
• Thus the roots of the second order Ordinary Differential Equation can be
denotes the modulus or the absolute value of the vector X, and θ denotes expressed as: e x = e − ( a / 2) x + i x = e − ( a / 2) x (cos x + i sin x)
1

the argument
g of the angle
g between the vector and the x axis,, then X can e 2x
= e −(a / 2) x−i x
= e − ( a / 2 ) x (cos x − i sin x )
also be expressed as:
• We now add these two lines and multiply the result by ½. This gives:
y1 = e − ax / 2 cos x
• Then we subtract the second line from the first and multiply the result by
1/2i. This gives: − ax / 2
y2 = e sin x
Homogeneous linear ODEs with
constant coefficients Nonhomogeneous ODEs
Choice rules for the method of undetermined coefficients
Case Roots Basis General solution
a) Basic rule: If r(x) is one of the functions in the first column in the Table,
I Distinct real
e 1x , e 2x
y = c1e 1x
+ c2 e 2x choose yp in the same line and determine its undetermined coefficients
λ1, λ2
by substituting yp and its derivatives into
y + p ( x) y + q ( x ) y = r ( x )
II Real double root
e − ax / 2 , xe − ax / 2 y = (c1 + c2 x )e − ax / 2 b) Modification rule: If a term in your choice for yp happens to be a solution
λ= a/2 of the homogeneous ODE corresponding to the above equation, multiply
III Complex yyour choice of yp byy x ((or x^2 if this solution corresponds
p to a double root
conjugate of the characteristic equation of the homogeneous ODE)
1 c) Sum rule: If r(x) is a sum of functions in the first column of the table,
1 = − a+i y1 = e − ax / 2 cos x
2 y = e − ax / 2 ( A cos x + B sin x) choose for yp the sum of the functions in the corresponding lines of the
1
a −i y2 = e − ax / 2 sin x second column.
2 = −
2

Nonhomogeneous ODEs
• In this
h section, we proceed
d from
f h
homogeneous to nonhomogeneous
h
ODEs.
y + p ( x ) y + q ( x) y = r ( x )

## • The general solution consists of two parts:

y ( x) = y h ( x ) + y p ( x)
where yh = c1 y1 + c2 y2 is a general solution of the homogeneous ODE.
ODE

## Term in r(x) Choice for yp(x)

x
ke Ce x
kx n (n = 0,1,2,...) K n x n + K n −1 x n −1 + .... + K1 x + K 0
k cos x K cos x + M sin x
k sin x
ke x cos x e x ( K cos x + M sin x)
x
ke sin x